Application of Markov chains in the prediction of rock slopes degradation - Tinoco, Joaquim Agostinho Barbosa (2015)
In this paper it is proposed a degradation model for rock slopes, which will integrate a global tool for sustainable management of road infrastructures, currently under development. The proposed model is based on a continue-time Markov chain and predicts the evolution of a Slope Quality Index (SQI) over time. Taking advantage of the memoryless property of Markov models, the proposed model is able to predict the next state only based on the current state, not depending on the sequence of events that preceded it. In addition, the effect of maintenance actions is also considered in the prediction of the state condition of a given slope. The achieved results, which represent a first iteration towards the development of a predictive model for rock slope degradation processes during its exploration phase, show that the use of Markov chains can lead to reliable results.